Case-Control Study: Evaluating the Role and Therapeutic Potential of FSTL1 in Type 2 Inflammation of Chronic Rhinosinusitis - Huang B; Zhu J; Chai X (Journal of Inflammation Research)
Bingjie Huang,1,2 Jingyun Zhu,1 Xiangbin Chai3 1First Clinical Medical College, Shanxi Medical University, Taiyuan, 030000, People’s Republic of China; 2Shanxi Key Laboratory of Otolaryngology Head and Neck Cancer, Taiyuan, 030000, People’s Republic of China; 3Department of Otolaryngology Head and Neck Surgery, The First Hospital of Shanxi Medical University, Taiyuan, 030000, People’s Republic of ChinaCorrespondence: Xiangbin Chai, Department of Otolaryngology Head and Neck Surgery, The First Hospital of Shanxi Medical University, Taiyuan, 030000, People’s Republic of China, Email cxb14001@163.comPurpose: Follicle suppressor-like protein 1 (FSTL1) plays a contributory role in chronic inflammation, and it currently been demonstrated in studies of asthma and chronic obstructive pulmonary disease (COPD), but studies in chronic sinusitis with nasal polyps have not been addressed. The aim of this study was to explore the expression of follicle suppressor-like protein 1 (FSTL1) in chronic sinusitis and its possible association with type 2 inflammation.Patients and Methods: This study included 34 CRS patients (24 ECRS, 10 non-ECRS) and 10 controls. Hematoxylin-eosin (HE) staining to observe the pathomorphological changes of these three groups of tissue specimens in detail, Immunohistochemistry (IHC), real-time quantitative reverse transcription-polymerase chain reaction (qRT-PCR) technology and Western blotting (WB) were used to evaluate the expression levels of FSTL1 and type 2 inflammatory cytokines IL-4, IL-5, and IL-13 in the three groups.Results: In the ECRS group, there was thickening of the tissue mucosa and hyperplasia of glands, along with a significant infiltration of inflammatory cells and eosinophils. The experimental results showed that the expression levels of FSTL1 and type 2 inflammatory cytokines IL - 4, IL - 5, and IL - 13 were higher in the ECRS and non - ECRS groups than in the control group (P< 0.05). Additionally, FSTL1 and IL-4, IL-5, IL-13 were positively correlated in the ECRS group(P< 0.05).Conclusion: FSTL1, IL-4, IL-5 and IL-13 were highly expressed in chronic sinusitis, and FSTL1 was positively correlated with IL-4, IL-5 and IL-13 in the ECRS group, suggesting that FSTL1 contributes to the development of type 2 inflammation in ECRS, and FSTL1 may serve as a potential therapeutic target for ECRS.Keywords: chronic sinusitis, follicle suppressor-like protein 1, type 2 inflammation